KERENTANAN EMPAT JENIS KAYU RIMBA TERHADAP SERANGAN JAMUR PEWARNA - Dominicus Martono (Jurnal Penelitian Hasil Hutan, 1989)
This study   evaluates  the  susceptibility   of  ramin (Gonystilus bancanus Kurz),  jelutung    (Dyera  sp),   mentibu   (Dacty- locladus  stenostachys  Oliv)  and  meranti   batu  (Shorea   sp)  against  sapstain.   The  material  used  consists  of  debarked   and unbarked   fresh  logs.  The  tested  logs  were  tried  at  swamp  forest   in  West  Kalimantan   in November   -   December   1978.The  data  were analysed  by  Nested   Classification  method.   The  degree  of  damage  was transformed   into  arcsin √%Inspections   were conducted   biweekly   for one month  after  treatment.The  result  showed  that  the  average degree  of  damage due    to  the sapstain  were  not  different  among  the four  wood species.  The effect  of debarking  treatment   increases the log susceptibility. There is no different of staining degree among  the log cutting  from  the  base, middle  and top of  the trees.